The Effect of Risk on Profitability in Islamic Banking - Kamilah, Athia Nur; Rinaima, Chetrine Alya; Fauziyah, Nur; Fitri, Rati Saktia (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This research focuses on the impact of credit and market risk, capital, and liquidity factors on the efficiency of Islamic banks operating under Government-Linked Companies (GLCs) in Malaysia. Based on Bank Islam Berhad, CIMB Islamic Berhad, and Maybank Islamic Berhad, the study examines how these variables influence profitability, measured by Return on Assets (ROA). Upon dealing with the quantitative approach, the findings contrast the literature in that risk constituents while varied in their significance have an equal significance on overall profitability. This study contributes to the literature on Islamic finance by providing practical recommendations for enhancing risk management and ensuring financial sustainability in the Islamic banking sector.